Physico-chemical investigation of the volatile oil of Myristica fragrans Houtt. (Fam. Myristicaceae) - Cammayo, Carlos M.; Bernal-Santos, Rizalina (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1977)
A clear, colorless essential oil which turns to pale yellow upon standing was obtained from the kernels of the dried ripe seed of Myristica fragrans Houtt. at an average yield of 5.73% (v/w). the nutmeg oil gave the following physicochemical constants: specific gravity, 0.8934 (25°C); optical rotation, 34.6435; specific rotation, 40.4230 (28°C); refractive index, 1.4761 (25°C); acid value, insignificant; ester value, 6.0
UV Spectrophotometric analysis of the components isolated by both preparative TLC and column chromatography indicates the possible presence of some terpenes as camphene, pinene. Camphene has been established to be present while the others have to be fully established further, using more accurate methods of analysi
Preparative TLC and column chromatography showed that the components corresponding to the absorbance of the oil (276 nm and 210 nm) can be separate
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman,1977.
Keywords: Myristicacea; Nutmeg tre; Essences and essential oil